Performative spaces in the work of Ann Veronica Janssens and Rafael Lozano-Hemmer - Cabañero, Jesús Segura; Mulet, Toni Simó (Advances in Social Sciences Research Journal, 2018)
The purpose of this article is to analyze the spatial and temporal relationships in the works of art of Ann Veronica Janssens and Rafael Lozano-Hemmer through the performative. We understand the performative, as a spatio-temporal artistic action that triggers perception, abstraction and political activation. The performative act between the work and the spectator is therefore the essential element of reflection. In the first part, we analyze the decelerated spaces of Ann Veronica Janssens, where the performativity of bodies in spaces and through an ephemeral materiality configures a space in constant transformation. In a second part, we analyze the relational spaces of Rafael Lozano-Hemmer. In his interactive installations, the performative forms an intrinsic part of the work, so that the meeting between the spectator and the work takes place temporarily. Finally, we conclude that these works of art produce a political activation of the environment that proposes the viewer as the true interlocutor who co-produces the work. This work is framed in the new spatio-temporal performativities in contemporary art.